2008
DOI: 10.1007/s11743-008-1098-y
|View full text |Cite
|
Sign up to set email alerts
|

Formulating Alcohol‐Free Microemulsions Using Rhamnolipid Biosurfactant and Rhamnolipid Mixtures

Abstract: This research focused on developing alcoholfree biosurfactant-based microemulsions. Rhamnolipidbased mixtures were found to have double the solubilization parameter as compared to sodium bis(2-ethyl) dihexyl sulfosuccinate/sodium dihexyl sulfosuccinate/sodium mono-and dimethyl naphthalene sulfonate at the same total molar concentration. For the first time, a phase diagram was developed for surfactant mixtures containing soy methyl ester ethoxylate, rhamnolipid and oleyl alcohol with limonene oil. This phase di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…The alkanols probably had been located in the polar phase (acted as solubilized substances) in competition with glycerol when they were solubilized in the RL based microemulsion. Microemulsion system formed by RL or RL mixture in the absence of cosurfactant had also been reported in many researches [21]. However, as the trends displayed in Fig.…”
Section: Effect Of Cosurfactantsupporting
confidence: 52%
“…The alkanols probably had been located in the polar phase (acted as solubilized substances) in competition with glycerol when they were solubilized in the RL based microemulsion. Microemulsion system formed by RL or RL mixture in the absence of cosurfactant had also been reported in many researches [21]. However, as the trends displayed in Fig.…”
Section: Effect Of Cosurfactantsupporting
confidence: 52%
“…As the salinity and surfactant concentration change as the wash cycle transitions to the rinse cycles, the contact angle is hypothesized to change, enhancing detachment of the residual oil left after snap-off. Elucidation of the exact effect and mechanism requires further study since it is not known whether a change in concentration with such extended surfactant mixtures results in species partitioning and formulation shifts as with conventional surfactants [40]; this is likely the case since extended surfactants have been recently shown to behave as the synthetic or natural ones [20,21,23,[41][42][43][44], with the exception of the temperature effect [45]. …”
Section: Effect Of the Surfactant System On Dynamic Contact Angle Andmentioning
confidence: 99%
“…Even though investigation and optimization of rhamnolipid production as well as product portfolio expansion represent an emerging research field, the most important strain for rhamnolipids'c ommercial production remains Pseudomonas aeruginosa [43 -46]. Rhamnolipids have an anionic character and Nguyen et al showed that they are hydrophilic surfactants [47,48], while their hydrophilicity-hydrophobicity balance (HLB) has been reported to be 22 -24b yX ie et al [49]. They have shown an excellent emulsifying potential with different compounds [50,51], and their antimicrobial activity against both fungi and bacteria has been confirmed [52,53].…”
Section: Rhamnolipidsmentioning
confidence: 99%